Mahmud al-kashgari's divanü lügati't-türk i-ii-iii (2024). azerbaijan national academy of sciences, nasimi institute of linguistics, baku: azerbaijan - Cemile (Uluslararası Türk Lehçe Araştırmaları Dergisi)
Divanu Lügati't Türk (DLT), written by Kashgarli Mahmud in the XI century, has been translated and printed into various languages and Turkic dialects over time. Khalid Said Khojayev is one of the important researchers working on DLT. The first translation of DLT from Arabic to Latin letters belongs to Khalid Said. Khalid Said's translation is important in terms of being the first translation of DLT in Latin script both in Azerbaijan Turkic and in the Turkic world. Khalid Said started the translation of the work in 1935 and finished the translation in 1936, but could not publish the work. The translation of DLT in Azerbaijani language was unearthed after 86 years. With the decision of the Presidium of the Azerbaijan National Academy of Sciences dated 29 January 2024, Nesimi was prepared for publication by the Institute of Linguistics. This study includes the introduction of the work published by the Presidium of the Azerbaijan National Academy of Sciences. In the study, the features of Khalid Said's translation of DLT, the edition and structure of the work were emphasised.